Factors Associated with Musculoskeletal Disorders in Convection Tailors - Desti Rahmayani; Henny Permatasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to provide an overview of the factors associated with musculoskeletal disorders in convection tailors. This study uses a systematic literature review. Based on the results of the review and review of 8 journal articles, it can be concluded that several factors that influence this musculoskeletal disorder are the length of time sitting, excessive workload, poor work posture, work stress, lack of adequate rest, length of time working as a convection tailor, risk factors ergonomics, work environment arrangements, work, and rest patterns, and lack of training on ergonomics and safe work practices. In conclusion, several socio-demographic factors influence the occurrence of musculoskeletal disorders, including gender, marital status, education level, BMI, physical exercise patterns, and medical history. Keywords: Musculoskeletal Disorders, Occupational Health Nursing, Sewing Machine Operators, Convection Tailors